Ultrasonic measurements of aqueous solutions of [ampersand]beta;-cyclodextrin with alkyl pyridinium bromides - Andrzej BALCERZAK (Archives of Acoustics)
Ultrasonic measurements of the velocity and absorption coefficient, [ampersand]alpha;/f2, of aqueous solutions of [ampersand]beta;-cyclodextrin with alkyl pyridinium bromides CnH2n+1C5H4NBr (n = 8, 10, 12), were carried out at the following temperatures: 288.2 K, 298.2 K, 308.2 K and 318.2 K, and frequency range from 1 MHz to 150 MHz. Concentration of the both components equaled 0.01 M. The occurrence of two ultrasonic relaxation processes has been reported. Thermodynamic and kinetic parameters related to these processes have been calculated. The obtained results have been compared with data published previously for [ampersand]alpha;-cyclodextrin systems.